The impact of sports industry agglomeration on the high-quality development of green energy - Luo, Min; Chen, Lingming (Frontiers in Environmental Science, 2023)
As China's economy has transitioned, the energy industry has developed rapidly. The government is promoting a revolution in energy production and consumption and building a green, low-carbon, safe and efficient energy system. The high-quality development of green energy has become an essential part of high-quality economic development. This paper constructs a high-quality green energy development indicator system from three aspects: green energy production, green energy output and pollution output. Then, the entropy weight method is used to measure the high-quality development level of inter-provincial green energy in China from 2010 to 2018.Moreover, the characteristics of regional differences and time evolution are deeply analyzed. Based on this, the impact of sports industry agglomeration on the high-quality development of green energy is verified. The results show that the aggregation of the sports industry can increase the level of high-quality development of green energy, and different regions have heterogeneous characteristics. Finally, based on the research conclusions, this paper puts forward some policy recommendations for promoting high-quality energy development in China.